Pentandricines F-H, cytotoxic limonoids from the stem bark of Chisocheton pentandrus (Blanco) Merr. (April 2023) - Harneti, Desi; Salam, Supriatno; Nurlelasari,; Maharani, Rani; Mayanti, Tri; Safari, Agus; Hidayat, Ace Tatang; Lesmana, Ronny; Fajriah, Sofa; Supratman, Unang; Prescott, Thomas; Shiono, Yoshihito
Abstract: Three new cedrelone-type limonoid derivatives, pentandricines F-H (1–3 ) along with four known limonoids (4–7) were isolated from the stembark of Chisocheton pentandrus (Blanco) Merr. Their chemical structures were fully elucidated by spectroscopic data. Compound 2 (pentandricine G) proved to be the most active compound with an IC50 value of 48.11 μM against MCF-7 breast cancer cells comparing favorably with cisplatin (53.32 μM). Graphical Abstract: ga1 Highlights: Seven limonoids (1 - 7 ), were isolated from Chisocheton pentandrus stem bark. The structures were fully elucidated by NMR and mass spectrometry. Limonoids (1 - 7 ), were evaluated for their cytotoxic effects against MCF-7 breast cancer cell. Pentandricine G (2 ), exhibited strongest activity with an IC50 value of 48.1 μM.